Asymmetrical effect of total quality management on organisational citizenship behaviour for the environment: mediated by environmental corporate social responsibility - Sahar, Noor E.; Zawawi, Dahlia; Jaharuddin, Nor Siah; Abbasi, Munir A. (Emerald, 2024)
Purpose The current study used the social exchange theory to examine the dimensional impact of total quality management (TQM) on the organisational citizenship behaviour for the environment (OCBE) of employees through the mediatory role of environmental corporate social responsibility (ECSR).